Investment on sport industry by the telecom operators of Bangladesh: an overview of Robi Axiata Limited - Sultan, Samira (BRAC University, 2018)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.